Hubungan antara aktivitas olahraga dengan ritme sirkadian dan stres - Poluakan, Ricko Johanes; Manampiring, Aaltje E.; Fatimawali, . (UNIVERSITAS SAM RATULANGI, 2020)
Abstract: The aims of this study to know the description and the relationship between sports activity, circadian rhythm, and stress. The method used is quantitative research. Sample were determine by the total sampling amounted to 60 in the interests of Occupational Health and Safety in the Faculty of Public Health Sam Ratulangi University class of 2017. Analysis of test data using spearman correlation coefficient. The results of the research is the activity of the sports category was 48.3%, low 20.7%, the category of circadian rhythm less 56.9%, and the category of bad 20.7%. Category of stress was 56.9%, lower 19.1%. Test spearman correlation coefficient found a significant relationship between sports activity with stress, is known to significant (2 tailed) i.e. 0.01 with the level of the strength of the relationship moderates as well as the direction of the relationship positive. Test spearman correlation coefficient between the circadian rhythm of stress found a significant relationship, it is known the value of significant (2 tailed) is 0.000 with the level of the strength of the relationship moderates as well as the direction of the relationship positive. Conclusion in this study is that there is a relationship between sports activity and circadian rhythm with the stress on the students evidenced significant.Keywords: sports activities, circadian rhythm, stressÂ Â Abstrak: Penelitian ini bertujuan untuk mengetahui gambaran dan hubungan antara aktivitas olahraga, ritme sirkadian dan stres. Metode yang digunakan yaitu jenis penelitian kuantitatif. Sampel ditentukan secara total sampling berjumlah 60 pada peminatan Kesehatan dan Keselamatan Kerja (K3) di Fakultas Kesehatan Masyarakat (FKM) Universitas Sam Ratulangi Angkatan 2017. Analisis data menggunakan uji koefisien korelasi spearman. Hasil penelitian ialah aktivitas olahraga kategori sedang 48.3%, rendah 20.7%, kategori ritme sirkadian kurang 56.9%, dan kategori buruk 20.7%. Kategori stres sedang 56.9%, rendah 19.1%. Uji koefisien korelasi spearman ditemukan adanya hubungan signifikan antara aktivitas olahraga dengan stres, diketahui nilai signifikan (2 tailed) yaitu 0.01 dengan tingkat kekuatan hubungan moderat serta arah hubungan positif. Uji koefisien korelasi spearman antara ritme sirkadian dengan stres ditemukan adanya hubungan yang signifikan, diketahui nilai signifikan (2 tailed) yaitu 0.000 dengan tingkat kekuatan hubungan moderat serta arah hubungan positif. Simpulan dalam penelitian ini ialah terdapat hubungan antara aktivitas olahraga dan ritme sirkadian dengan stres pada mahasiswa dibuktikan signifikan. Â Kata kunci: aktivitas olahraga, ritme sirkadian, stres